2019
DOI: 10.3390/su11205854
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Environmental Performance of a Product/Service-System Business Model for Merino Wool Next-to-Skin Garments: The Case of Armadillo Merino®

Abstract: Circular business models are often enabled by means of product/service-systems (PSS). The common perception is that such business models have enhanced environmental performance when compared to conventional business models rooted in the linear economy. This article investigates the environmental potential of developing a use-oriented PSS business model for Merino wool t-shirts intended for use by the British Ministry of Defence as an alternative to the present supply system based on synthetic t-shirts purchase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…-T-shirt Product-Service System (PSS)- [7] Quantify and compare impacts in two different systems. Method: LCA Environmental impact is reduced if a circular PSS is proposed.…”
Section: Service System Objective and Methods Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…-T-shirt Product-Service System (PSS)- [7] Quantify and compare impacts in two different systems. Method: LCA Environmental impact is reduced if a circular PSS is proposed.…”
Section: Service System Objective and Methods Resultsmentioning
confidence: 99%
“…Activities conducted in service creation and actions developed when a service operation is finished are rarely considered. We reviewed recent studies on sustainability in service systems [4][5][6][7][8][9] (Table 1) and observed the following: they frequently compare impacts of alternatives as a research objective, their sustainability results focus on the environmental dimension, and in only a few cases were socioeconomic data obtained.…”
Section: Advances In the Design Of Sustainable Servicesmentioning
confidence: 99%
“…Although this example was unable to meet all its desired goals over its full life cycle, it represents a proof of concept that warrants further research and could present multiple benefits through the lowering of direct resource inputs and reduction in waste products. Cyclical flow is at the core of the endeavour, which resonates widely with various infrastructure-based attempts to move toward a more circular economy rather than a 'take-make-dispose' model (Bech et al 2019). More broadly, the pursuit of urban agriculture has benefits in the production of food closer to points of demand, reducing monetary and environmental transport costs and making greater use of local resources that may otherwise be treated as waste, such as rain runoff (Al-Kodmany 2018).…”
Section: Case Study: Circular Resource Model For Urban Agriculturementioning
confidence: 97%
“…Spatial interaction in the urban suburbs of Metropolitan Mamminasata is influenced by four main factors, namely (i) spatial integration of core cities and supporting cities, (ii) differentiation and specialization of urban systems, (iii) organizing urban activities as a single spatial system, and (iv) distribution of goods and services from one node to another node. Circular economy is often seen as an environmental superior alternative to the take-make-dispose linear economy [103]. Thus, it can be concluded that urban systems that are built in the periphery are inseparable due to economic growth and spatial planning, both of which are interrelated and influence factors between one activity and another.…”
Section: Urban Agglomeration and Economic Growthmentioning
confidence: 99%